An expert opinion assessment of blood‐feeding arthropods based on their capacity to transmit African swine fever virus in Metropolitan France. Issue 3 (24th August 2020) - Saegerman, Claude; Bonnet, Sarah; Bouhsira, Emilie; De Regge, Nick; Fite, Johanna; Etoré, Florence; Garigliany, Mutien‐Marie; Jori, Ferran; Lempereur, Laetitia; Le Potier, Marie‐Frédérique; Quillery, Elsa; Vergne, Timothée; et al.
Abstract: To deal with the limited literature data on the vectorial capacity of blood‐feeding arthropods (BFAs) and their role in the transmission of African swine fever virus (ASFV) in Metropolitan France, a dedicated working group of the French Agency for Food, Environmental and Occupational Health & Safety performed an expert knowledge elicitation. In total, 15 different BFAs were selected as potential vectors by the ad hoc working group involved. Ten criteria were considered to define the vectorial capacity: vectorial competence, current abundance, expected temporal abundance, spatial distribution, longevity, biting rate, active dispersal capacity, trophic preferences for Suidae, probability of contact with domestic pigs and probability of contact with wild boar. Fourteen experts participated to the elicitation. For each BFA, experts proposed a score (between 0 and 3) for each of the above criteria with an index of uncertainty (between 1 and 4). Overall, all experts gave a weight for all criteria (by distributing 100 marbles). A global weighted sum of score per BFA was calculated permitting to rank the different BFAs in decreasing order. Finally, a regression tree analysis was used to group those BFAs with comparable likelihood to play a role in ASF transmission. Out of the ten considered criteria, the experts indicated vectorial competence, abundance and biting rate as the most important criteria. In the context of Metropolitan France, the stable fly ( Stomoxys calcitrans ) was ranked as the most probable BFA to be a vector of ASFV, followed by lice ( Haematopinus suis ), mosquitoes ( Aedes, Culex and Anopheles ), Culicoides and Tabanidea . Since scientific knowledge on their vectorial competence for ASF is scarce and associated uncertainty on expert elicitation moderate to high, more studies are however requested to investigate the potential vector role of these BFAs could have in ASFV spread, starting with Stomoxys calcitrans .